GEDUNG PERTUNJUKAN MUSIK MODERN DENGAN PENDEKATAN ARSITEKTUR EKSPRESIONISME DI SURAKARTA - Dhita Fardaniwuri; Suparno Suparno; Hari Yuliarso (ARSITEKTURA, 2016)
Surakarta is a city of art and culture. In accordance with the development of more advanced age, the development of music in Surakarta is also increasing, especially in modern music. Surakarta society has a high appreciation of the music that can be seen from the many festival band events and also modern music performances were held. The existence of places to perform the music in Surakarta has not meet the standards and requirements of the theater and also not representative enough in terms of architecture, so the purpose of this scheme is to obtain a building design that gives a forum for people to express their musical taste or become a means of entertainment to enjoy music itself. Modern Music Concert Hall in Surakarta is expected to facilitate the activities of modern music performances which are supported by relevant supporting facilities located in Surakarta. The issue is how the design of musical expression can be translated into the design of Modern Music Concert Hall using architectural design. The design of the building will show the expression and characteristics of modern music. Submission of image expression form, shown by the arrangement embodied in the design appearance of the building, the design of interior, exterior and support facilities of the building so that the building can reflect the activities in it..   Keywords: Auditorium, expressionism, modern music, music concert hall